Perencanaan Penataan Jalan Akasia Guna Meningkatkan Kinerja Simpang Jalan Akasia - Jalan Akasia XVI - Putu Ika Wahyuni; Putu Ayu Sriasih Wesna; I Wayan Muliawan (Universitas Warmadewa, 2021)
Warmadewa University is a large university in Bali which has 7 Faculties, Study Programs and Postgraduate Programs. Warmadewa University has tens of thousands of active students from all existing Study Programs. Currently Warmadewa University operation is still centered on Jalan Terompong Number 24, Denpasar and has 3 exits, namely the main Akasia Street, XVI Akasia Street, and Akasia Street which is Ex IKIP / Paud Erlangga. Development of Univ. Warmadewa, which was founded in 1984, has brought rapid changes to the surrounding lands, which used to be agricultural land, now a densely populated settlement, boarding houses for students, shop, photocopying, laundry, and others which are significant changes due to the Warmadewa Campus. The condition of economic development around Warmadewa University can be seen from the increase in the number of stalls and shops which has an impact on the density of parking and traffic around it. Increasingly, this condition is getting denser without being accompanied by improvements in road facilities which are the main challenges in this PKM. Furthermore, the solution that can be offered is to carry out the physical arrangement of Jl. Main Akasia and Akasia XVI with the hope of creating a smooth flow of traffic at the intersection of the Akasia road with jl. Akasia XVI so that Warmadewa University as the center of economic revival can also help the surrounding community.